DEVELOPMENT OF INTERACTIVE DIGITAL COMICS ON SIMPLE PLANE TOPICS ON EMPOWERING STUDENTS' THINKING ABILITIES - Olivia Mogot; Mariana Rengkuan; Aswin Mandolang (Journal of Artificial Intelligence and Digital Economy, 2024)
The purpose of the research was to develop interactive digital comics about simple machines and to investigate the effect for using interactive digital comics in student thinking skills at grade VIII. The hypothesis of this research was that using interactive digital comics in simple machines gave a significant effect to student thinking skills. This type of research was development research, which refers to the Four-D (Define, design, develop, disseminate). The result shows simple machine digital interactive comic is categorized as valid and feasible because of the percentage of expert media judgment is 98.91% and the percentage of expert material judgment is 98.21%. In practicality test, this is indicated by the good response from students with a percentage of 82.44% in the limited trial class and 77.81% in the extended trial class. The Effectiveness, indicated by statistics analyzing the pretest and posttest of control and experimental groups. The test analysis with Wilcoxon test. The Wilcoxon test shows Asymp. Sig (2 tailed) < 0.001 which is less than 0.005 that means the hypothesis is accepted and proven.